2015
DOI: 10.15740/has/fsrj/6.2/273-278
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ingredients in cereal bar

Abstract: The objective of this study was the optimization of ingredient in RTE cereal bar using corn syrup and honey in different ratios. Organoleptic evaluation of RTE cereal bar was done by a panel of ten judges using 9 point hedonic scale. Results showed that 30 per cent incorporation level of corn syrup and honey in cereal bar obtained the highest overall acceptability i.e., CCB (8.39 ± 0.08), HCB (8.18 ± 0.14) and the score was in the range of "like very much" to "like extremely". Thus it can be concluded that 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Related results can be found in the development of cereal and granola bars prepared using sucrose alternatives ( Sethupathy et al. 2020 ; Torres et al., 2011 ; Yadav and Bhatnagar, 2015 ). In this study, increasing sweeteners caused the cereal bar to have a soft and sticky texture because of the hygroscopic nature of polysaccharides that results in absorption of moisture ( Shourideh et al., 2012 ).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Related results can be found in the development of cereal and granola bars prepared using sucrose alternatives ( Sethupathy et al. 2020 ; Torres et al., 2011 ; Yadav and Bhatnagar, 2015 ). In this study, increasing sweeteners caused the cereal bar to have a soft and sticky texture because of the hygroscopic nature of polysaccharides that results in absorption of moisture ( Shourideh et al., 2012 ).…”
Section: Resultsmentioning
confidence: 67%
“…(2015) , Megala and Hymavathi (2011) , Srebernich et al. (2016) , and Yadav and Bhatnagar (2015) which suggested that there are many ingredients such as puffed rice, roasted nut, cereal seed, mixed fruits, and sugar which can affect the consumer acceptance, product acceptance, and purchase intention of cereal bars. Those ingredients can cause variation in texture, flavor, crispiness, and sweetness in the higher gross energy cereal bars developed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These bars provide good sensory and nutritional characteristics due to the presence of carbohydrate, lipids, proteins and minerals in them. The changes in life style and dietary pattern, increasing awareness about healthy food habits with adequate nutritional requirements and increased physical activity has made energy bars a perfect choice as a quality source of energy [7].…”
Section: Introductionmentioning
confidence: 99%
“…The faster developing change in life style leads to rapid increase demand for the processed and convenience foods. Energy bars are one of the nutritionally balanced convenient food which has foothold since after 1980s (Mridula et al, 2011 andBhatnagar, 2015).…”
Section: Introductionmentioning
confidence: 99%